Pedicled forehead flap for the reconstruction of maxillary defect: A novel surgical case report - Sudipto Sahu; Subrat Padhiary; Rajarshi Banerjee; Sucharu Ghosh (Wolters Kluwer Medknow Publications, 2018)
"The tint of the forehead so exactly matches that of the face and nose that it must be the first choice" -Sir Harold Gillies and D. Ralph Millard Flaps from the frontal and temporal region have been used for mid-face, orbital, and peri-orbital reconstruction. The knowledge of the vascular anatomy of the region helps to dissect and harvest the muscle/fascia/skin/combined tissue flaps from that region depending on the requirement. Maxillectomy defects are usually covered with free flaps to fill the cavity. Here, we report an innovative technique in which a patient with a maxillectomy with external skin defect was covered with pedicled forehead flap based on the parietal and frontal branches of superficial temporal artery.